Fetal posterior cerebral artery configurations in an ischemic stroke versus an unselected hospital population. (22nd November 2021) - Frid, Petrea; Wasselius, Johan; Drake, Mattias; Wu, Ona; Petersson, Jesper; Rost, Natalia S.; Lindgren, Arne; ,
Abstract : Background: Few MRA‐based studies have systematically evaluated the prevalence and laterality of a fetal configuration of the posterior cerebral artery (FTP) in ischemic stroke populations versus other populations. This common variant is important in the setting of acute stroke and secondary prevention decisions. Objective: To determine the prevalence and laterality of FTP configurations in MRI‐DWI verified acute ischemic stroke patients investigated with MRA, and compare the findings with an unselected hospital population investigated with computed tomography angiography (CTA). We also evaluated the association of FTP with posterior cerebral artery (PCA) territory infarctions. Methods: We reviewed the MRAs of 1407 ischemic stroke patients with acute lesions on MRI‐DWI sequences and 546 consecutive CTAs of patients investigated on any indication in a tertiary hospital. The MRA and CTA assessments were made by neuroradiologists blinded to original reports on stroke location and vessel anatomy. Results: The prevalence of any FTP was similar in ischemic stroke patients (31%) and unselected patients (32%). Unilateral FTP was significantly more frequent on the right than on the left side in both groups (15% right vs. 8% left). The presence of FTP ipsilateral to stroke side was not associated with involvement of the PCA territory versus no FTP on the stroke side. Conclusions: FTP is present in approximately 30% of ischemic stroke patients and unselected hospital populations and was detected significantly more frequently on the right versus left side in both groups. PCA territory infarction was not associated with the presence of ipsilateral FTP.